Biological rationale and potential clinical use of gabapentin and pregabalin in bipolar disorder, insomnia and anxiety: protocol for a systematic review and meta-analysis. Issue 3 (27th March 2017) - Houghton, Kerensa T; Forrest, Alexandra; Awad, Amine; Atkinson, Lauren Z; Stockton, Sarah; Harrison, Paul J; Geddes, John R; Cipriani, Andrea
Abstract : Introduction: Gabapentin has been extensively prescribed off-label for psychiatric indications, with little established evidence of efficacy. Gabapentin and pregabalin, a very similar drug with the same mechanism of action, bind to a subunit of voltage-dependent calcium channels which are implicated in the aetiopathogenesis of bipolar disorder, anxiety and insomnia. This systematic review and meta-analysis aims to collect and critically appraise all the available evidence about the efficacy and tolerability of gabapentin and pregabalin in the treatment of bipolar disorder, insomnia and anxiety. Methods and analysis: We will include all randomised controlled trials (RCTs) reported as double-blind and comparing gabapentin or pregabalin with placebo or any other active pharmacological treatment (any preparation, dose, frequency, route of delivery or setting) in patients with bipolar disorder, anxiety or insomnia. For consideration of adverse effects (tolerability), single-blind or open-label RCTs and non-randomised evidence will also be summarised. The main outcomes will be efficacy (measured as dichotomous and continuous outcome) and acceptability (proportion of patients who dropped out of the allocated treatment). Published and unpublished studies will be sought through relevant database searches, trial registries and websites; all reference selection and data extraction will be conducted by at least 2 independent reviewers. We will conduct a random-effects meta-analysis to synthesise all evidence for each outcome. Heterogeneity between studies will be investigated by the I 2 statistic. Data from included studies will be entered into a funnel plot for investigation of small-study effects. No subgroup analysis will be undertaken, but we will carry out sensitivity analyses about combination treatment, psychiatric comorbidity, use of rescue medications and fixed versus random-effects model. Ethics and dissemination: This review does not require ethical approval. This protocol has been registered on PROSPERO (CRD42016041802). The results of the systematic review will be disseminated via publication in a peer-reviewed journal.